The Influence of Brand Equity on Consumer Purchase Decisions at Starbucks - D, Dilip; Sinha, Rupesh; Wen, Chin Pei; Kee, Daisy Mui Hung; Ching, Choong Shu; Er, Lew Ke; Agarwal, Somya; Pandey, Rudresh; Putra, Theofilus Welyna; Sin, Liem Gai; Yan, Yap Wen (AIBPM Publisher, 2021)
The purpose of this research is to study the influence of brand equity on consumer purchase decisions at Starbucks. Specifically, we predicted the brand equity of Starbucks would definitely affect the consumer purchase decisions. We distributed survey questionnaire consisting of 4 major aspects of brand equity with purchase decision and the results collected were analysed in order to obtain a meaningful conclusion. For the implementing, we designed a conceptual framework and hypothesized the correlation among its constructs which are brand equity and purchase intention. All the hypothesis which are tested based on the brand equity and consumer purchase decisions was accepted. The results showed that brand equity has a positive influence on consumer purchase decisions.